Labor Demand Effects of Rising Electricity Prices: Evidence for Germany - Michael Cox; Andreas Peichl; Nico Pestel; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2013)
Germany plays a pioneering role in replacing conventional power plants with renewable energy sources. While this is beneficial with respect to environmental quality, the energy turnaround implies increasing electricity prices for private households and firms. The extent to which this is associated with negative impacts on employment depends on the interrelationship between labor and electricity as input factors. In this paper, we estimate cross-price elasticities between electricity and heterogeneous labor for the German manufacturing sector. We use administrative linked employer-employee micro data combined with information on electricity prices and usage during the period 2003-2007. Our findings suggest that there is a weak substitutability between electricity and labor, when the production level is held constant. We find positive, but small conditional cross-price elasticities of labor demand with respect to electricity prices between 0.09 and 0.31. In case of adjustable output, we find moderate gross complementarity with negative unconditional cross-elasticities ranging between -0.06 and -0.69. Labor demand is affected differently across skill levels with low- and high-skilled workers being affected more than medium-skilled. Our estimates suggest that the announced increase of the EEG surcharge in 2014 would decrease overall employment in the manufacturing sector by 86,000 workers, a decline by 1.4 percent.
Keywords: J08; J23; Q48; Q58; 330; electricity prices; labor demand; employment; energy; Germany